Le mouvement #MeToo des deux côtés des Alpes à l’aune des discours Twitter : une analyse socio-discursive outillée de #BalanceTonPorc et #quellavoltache - Vercelli, Elena Margherita (Verbum – Analecta Neolatina, 2024)
The research aims to contribute to the understanding of cultural differences between France and Italy. In particular, the main objective is to observe how the #MeToo phenomenon took shape through the textual expressions of two different languages and cultures, in order to highlight that the different national articulations of the movement and the diverse responses to the issue of violence against women are shaped by the culture and social reality of Internet users. To achieve this, two comparable corpora of tweets were created, one in Italian and the other in French, which were then analysed to identify the dominant opinions contained in them and to trace from these the cultural specificities of the debate on gender-based forms of violence and harassment.